PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA SMA - Rina Widiana; Ade Dewi Maharani; Rowdoh Rowdoh (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Previously, the literacy skill of students class XI at SMAN 1 Lembah Melintang Pasaman Barat Regency was still low. The students only memorized concepts and theories so that they were not able to implement the concepts in their life. The research aimed at investigating the effect of the application of the Problem Based Learning on students' literacy skill. This research have been used Randomized Control Group Posttest Only Design. The sample of this research was high school students in class XI taken using simple random sampling. The data were analyzed with Mann Whitney test. The result shows the increase of the students’ average literacy skill after being taught with Problem Based Learning in the affective, cognitive, and psychomotor domains. It can be concluded that the Problem Based Learning Model is effective on the students’ scientific literacy skill in class XI of SMAN 1 Lembah Melintang Pasaman Barat.